Reconceptualizing Integrity Crisis Management in State-Owned Enterprises: A Multi-Stakeholder Perspective on the 2025 Fuel Adulteration Scandal - Aulia, Gita Cahya; Arsitatri, Zachwa Maulani Salsabilla; Fitri, Nurul Aprilia; Ananda, Muhammad Rifqy; Subrata, Pramudya Ibnu (Jurnal Genesis Indonesia, 2026)
This research explores the critical shift in crisis communication management within State-Owned Enterprises (SOEs), focusing on PT Pertamina (Persero) during the 2025 fuel contamination crisis. The study aims to bridge the gap between Situational Crisis Communication Theory (SCCT) and the unique socio-political burdens faced by state entities by proposing a new framework, the "Radical Accountability" model. Utilizing a qualitative conceptual approach, the methodology employs integrative literature synthesis and narrative case deconstruction. Data from secondary sources, including official corporate reports, social media discourse on TikTok and X, and reputable academic journals, were triangulated to identify systemic patterns of communication failure and the "transparency paradox" inherent in highly regulated industries. Findings reveal that moral integrity crises in SOEs trigger extreme public anger and "ontological insecurity" that conventional technical accidental models cannot resolve. The analysis identifies a structural conflict where bureaucratic rigidity and state secrecy collide with the public's demand for instant digital accountability. To address this, the proposed "Integrity Recovery Model" offers a three-phase strategic response: immediate symbolic action, systematic legal accountability, and the restoration of public sovereignty. This article extends SCCT by integrating energy sovereignty and moral integrity as core reputational assets. It shifts the role of Public Relations from reactive image management to evidence-based trust facilitation, providing a strategic blueprint for SOEs to navigate digital firestorms in the post-truth era by aligning communication narratives with tangible judicial interventions.